Evaluasi Kinerja Unit Crushing Plant Untuk Mencapai Target Produksi di PT. Sugih Alamanugroho, Kabupaten Gunung Kidul, Provinsi Daerah Istimewa Yogyakarta - Desri, M. Asron (Retii, 2024)
PT. Sugih Alamanugroho is a company that operates in the mining and processing of limestone. The limestone processing factory is located in Bedoyo Village, Ponjong District, Gunung Kidul Regency, Yogyakarta Special Region Province. This research was conducted to understand the technical aspects of the processing unit and provide alternative improvements that can be made to achieve the ideal daily production target. The research results show that the employee's working time schedule is 14 working hours. The reduction in time for obstacles that cannot be avoided is 32.1 minutes and obstacles that can be avoided is 437.8 minutes. Jaw Crusher tool availability value, Mechanical Availability 100%, Use Availability 58%, Physical Availability 100%, Effective Utilization 58%. Hammer Crusher, Mechanical Availability 100%, Use Availability 58%, Physical Availability 100%, Effective Utilization 58%. Pulverizer, Mechanical Availability 95%, Use Availability 59%, Physical Availability 97%, Effective Utilization 58%. Hourly production from processing equipment is 6.18 tons/hour, product details < 0.150 mm are 6 tons/hour or 97%, products measuring 0.105-149 mm are 0.18 tons/hour or 3%. Effective working hours are 13.5 hours per day producing 83.4 tons/day. Production results of 83.4 tons/day have not reached the production target of 100 tons/day. After the evaluation is carried out, to increase production results in order to achieve production targets is by improving employee working time scheduling to 18 working hours. Then the time for obstacles that cannot be avoided becomes 30 minutes and obstacles that can be avoided is 0 minutes. Furthermore, improvements to the value of Jaw Crusher tool availability, Mechanical Availability 100%, Use Availability 96%, Physical Availability 100%, Effective Utilization 96%. Hammer Crusher, Mechanical Availability 100%, Use Availability 96%, Physical Availability 100%, Effective Utilization 96%. Pulverizer, Mechanical Availability 96%, Use Availability 100%, Physical Availability 97%, Effective Utilization 96%. The production per hour from processing equipment that can be achieved is 6.18 tons/hour, product details < 0.150 mm is 6 tons/hour or 97%, products measuring 0.105-149 mm are 0.18 tons/hour or 3%. For effective working hours of 17.5 hours per day producing 108.5 tons/day. The production results from the improvement alternative were 108.5 tons/day, which has reached the production target of 100 tons/day.